Developing scriptural agency through participatory action research embedded in service learning - Jaffer, Saleemah; Bayat, Abdullah (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
The paper reports on students at an Islamic higher education institute in South Africa who were enrolled in a service learning module to see whether this led to augmentation in their agency. In the service learning (SL) module, the students were tasked with using community-based participatory action research (CBPAR) which enabled them to make reflective decisions which is the basis of their augmented agency. The research method was a self-study case study. Implications for religious institutions is that they are encouraged to include service learning in their curriculum. The implication for students is that learning faith is about living the faith in context. Lecturers need to shift their pedagogy and teach the faith in an applied manner beyond traditional rote learning. Pedagogic insights included the important role of self-reflection and the activation of student agency through community engagement. Students found participating with community members empowering. Students enjoyed the experience and found the opportunity to transfer scripture into service learning invaluable. They realised their ability to make a change, lived their scripture, and the community benefited from this. Artikel ini menjelaskan tentang mahasiswa di sebuah lembaga pendidikan tinggi keislaman di Afrika Selatan yang mengikuti modul pembelajaran pengabdian untuk melihat apakah hal ini dapat meningkatkan kepemimpinan mereka. Dalam modul pembelajaran pengabdian/service learning (SL), para mahasiswa ditugaskan untuk menggunakan penelitian tindakan partisipatif berbasis masyarakat (CBPAR) yang memungkinkan mereka untuk membuat keputusan reflektif yang merupakan dasar bagi peningkatan kepemimpinan mereka. Metode penelitian yang digunakan adalah studi kasus belajar mandiri. Implikasi riset ini bagi lembaga keagamaan adalah bahwa mereka didorong untuk memasukkan pembelajaran pengabdian dalam kurikulum mereka. Implikasi bagi mahasiswa adalah belajar tentang iman berarti bagaimana mengamalkan iman dalam keseharian. Para dosen perlu mengubah pengajaran mereka dan mengajarkan iman dengan cara yang lebih dari sekadar hafalan. Wawasan pedagogis termasuk peran penting dari refleksi diri dan aktivasi kepemimpinan mahasiswa melalui keterlibatan masyarakat. Para mahasiswa merasa bahwa berpartisipasi dengan anggota masyarakat sangat memberdayakan. Mereka menikmati pengalaman ini dan menemukan bahwa kesempatan untuk mengamalkan kitab sucinya ke dalam pembelajaran pengabdian sangat berharga. Mereka menyadari kemampuan mereka untuk membuat perubahan, menghayati kitab suci, dan masyarakat mendapat manfaat dari hal ini.